Kajian Struktural Terhadap Puisi “Masyiatullah” Karya Imam Syafi’i - Izzatunisa, Muthi’ah Izzatunisa; Febriani, Nafi; Ridwan, Nur Anisa (Prosiding Konferensi Nasional Bahasa Arab, 2023)
The purpose of writing this article is to find out the intrinsic elements in Imam Syafi'i's poementitled